Heat transfer in turbulent nanofluids: Separation flow studies and development of novel correlations / Elham Montazer - Elham , Montazer (2019)
Convective heat transfer plays a significant role in many industrial heating and cooling applications. This mode of heat transfer can be passively enhanced by reconfiguring flow passage, boundary conditions, or fluid thermophysical properties. The broader scope of nanotechnology initiated many studies of heat transfer and thermal engineering. Nano fluids are one of such technology which can be thought of engineered colloidal fluids with nano-sized particles. Experimental investigation on turbulent forced convection heat transfer to nanofluids in an axisymmetric abrupt expansion has conducted in this research work. A number of studies on the effect of nanofluids on heat transfer augmentation have taken care in addition to the investigation of rearrangement on flow passage configurations. In heat transfer investigation, this study has focused on functionalized multiwalled carbon nanotubes (MWCNT-COOH), polycarboxylate functionalized graphene nanoplatelets (F-GNP), SiO2 and ZnO water based nanofluids. In this investigation the convective heat transfer coefficient and friction factor at fully developed turbulent flow of nanofluids flowing through the sudden expansion with the expansion ratio (ER) of 2 was experimentally determined at constant wall heat flux of 12,128.56 W/m2 . The experiments were conducted at the Reynolds number range of 4,000–16,000. The observed Nusselt numbers are greater than data obtained in the fully developed pipe flow which indicates that the level of the turbulent transport is high even though the recirculating velocities are a few percentages of the bulk mean velocity. This feature supports the existence of the turbulent transport processes in the recirculating flows. The influence of the volume fraction of nanofluids and Reynolds number on heat transfer and friction losses were examined. All the results reveal that the enhancement of weight concentration and Reynolds number, augments the local Nusselt number with the increment of axial ratios in all the cases which is representing higher heat transfer rates than that of base fluid. Results show that the maximum Nu were occurred at the distance of almost ten times step height in the downstream zone. Comparison between the examined four types of nanofluids, show that the carbon-based nanofluids have a greater effect on enhancing heat transfer (33.7% and 16.7% heat transfer performance improvement for F-GNP and MWCNT nanofluids respectively at 0.1 wt% concentration) at the downstream of the sudden expansion pipe. In general, none of the existing correlations appear entirely satisfactory for the general use in the sudden expansion of pipe. Last part of the present study was undertaken for developing more generally applicable correlations, based on the research concepts. In conclusion, three applicable correlations for the average Nu, f and local Nu have proposed whereas the first two correlations predict the average Nu and friction factor relating Re, Pr and volume fraction with reasonably good accuracy. There is no available work dealing with the prediction of the local Nu with the distance of the axial ratio of flow through sudden expansion. So, the third correlation which is proposed for the first time, expresses the local Nu versus axial ratio, Re, Pr and volume fraction of nanoparticles acceptable for the base fluid and the nanofluids. This correlation has satisfied the data from all the considered sources rather than from just one or two of the sources.